Volume and distribution of white matter hyperintensities in rheumatoid arthritis and ulcerative colitis patients - Jennifer G. Cox; James H. Cole; Matthew J. Kempton; Steven C. R. Williams; Marius de Groot (Scientific Reports)
Abstract Brain white matter disruptions have been implicated in contributing to fatigue, brain fog and other central symptoms commonly reported in inflammatory diseases. In this study, we included 252 RA patients with 756 age and sex matched controls and 240 UC patients with 720 age and sex matched controls using the UK Biobank imaging dataset. We looked for differences in total volume of white matter hyperintensities (WMH) between patients compared to controls. Then, using voxelwise analysis, we explored the spatial distribution of these white matter hyperintensities and differences in these between patients and controls and between disease groups. A significantly higher volume of WMH was observed in both the RA (p = 1.9 × 10−8, β =  − 0.36, 95% CI =  − 0.48, − 0.23) and UC (p = 0.003, β =  − 0.18 95% CI =  − 0.31, − 0.06) patients compared to their respective control groups. Voxelwise analysis revealed only a small cluster of RA associated WMH compared to controls. These results indicate an increased risk of white matter hyperintensities in patients with RA and UC. These findings help quantify the effect of inflammation from autoimmune diseases on cerebrovascular health and white matter integrity.